2022
DOI: 10.1186/s12872-022-02720-8
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model linking health literacy, self efficacy and quality of life in adults with coronary heart disease

Abstract: Background Cardiovascular disease is the world major cause of death. There is sufficient evidence that patients with coronary heart disease (CHD) experience poor quality of life. Health literacy and self efficacy are modifiable psychosocial factors that could affect quality of life, and these factors should be considered as targets for intervention. As the relationships among health literacy, self efficacy, and quality of life in the CHD population have not been well understood. Thus, we constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…A longer Reference value > 0.9 < 0.05 > 0.9 > 0.9 > 0.9 > 0.9 > 400 disease duration may increase the accessibility of health education and eventually enhance the skills required for disease knowledge and information. Finally, the negative relationships between HL scores and BMI were congruent with previous findings [18]. The negative correlation between HL and BMI suggests that patients with high HL have healthier lifestyles [36].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A longer Reference value > 0.9 < 0.05 > 0.9 > 0.9 > 0.9 > 0.9 > 400 disease duration may increase the accessibility of health education and eventually enhance the skills required for disease knowledge and information. Finally, the negative relationships between HL scores and BMI were congruent with previous findings [18]. The negative correlation between HL and BMI suggests that patients with high HL have healthier lifestyles [36].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have demonstrated that patients with low HL may be less concerned about their health status and therefore engage in unhealthy behavioral patterns that lead to a reduced QOL [15]. Similar studies have also suggested that HL can influence patients' QOL through self-efficacy (SE) [16][17][18]. SE is an individual's belief in their ability to plan and execute a specific course of action [19].…”
Section: Introductionmentioning
confidence: 99%
“…In 89 relevant papers in HL, studies authored by Chinese scientists are the most prevalent, with 27 studies that surveyed HL levels in various groups of people. They were patients 22 -27 or general public, secondary, 28 -30 high school, 30,31 college students, 32,33 women, 34 12 years old and above, 16,15,35 -43 or older adults. 44 -47 Taiwan had the second-highest number of HL measurement articles, with 16 published papers.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, higher levels of general self-efficacy were associated with higher levels of health literacy in all statistical models. In other populations, an association between self-efficacy and health literacy has been identified for patients with diabetes 39 , 40 , patients with coronary disease 41 , patients in cardiac rehabilitation 42 , and older adults with hypertension 43 . In stroke survivors, a previous study found a positive association between health literacy and self-efficacy in the use and understanding of medication 44 .…”
Section: Discussionmentioning
confidence: 99%